Impacts of leaf extract of Catharanthus roseus (L.) on seed mycoflora of soybean - Pawar, P V; Muley, S M (Current Botany, 2012)
Present research communication deals with study impact of Catharanthus roseus (L.) leaf extract on seed borne fungi of soybean seeds.